Рец.: на монографию «Златната Орда и Българите». Пламен Павлов, Георги Владимиров. – 175 с. (на болгарском языке) - Евглевский, А.В. (Степи Европы в эпоху средневековья, 2012)
This paper is a review of the book “The Golden Horde and Bulgarians" written by the Bulgarian scholars Plamen Pavlov and Georgy Vladimirov. It is devoted to the hotly debated problem of the ethnocultural relationship of the Danube and Volga Bulgarians in the time of the Golden Horde. The monograph considers a wide range of problems concerning the culture of the Bulgarians within the context of their political history. It can be positively stated that the book will work well as an excellent specialized textbook for Bulgarian students as well as those from the former USSR countries. The book (especially its fifth chapter, which touches upon the most debatable and the least developed issues discussed in literature) can also be interesting for specialists. On the other hand, the book is not devoid of drawbacks. The biggest of them is the lack of quotations from the newest literature on the subject.